Predict the location of moving objects using mining association rules of movement patterns - Nguyen, Phuong Tien; Dang, Duc Van (Journal of Computer Science and Cybernetics, 2013)
A location-based service is an information and entertainmentservice, accessible with mobile devices through the mobile network andutilizing the ability to make use of the geographical position of the mobile device. Location-Based Services report the current location of the user. In order to support context-prediction and proactive devices, location-based services must be able to predict locations. In the world, there are many research issues of predicting the location of the moving objects. Some issuestowards studying fuzzy logic, statistical probability or combining different methods. The goal of this paper is to introduce a framework for pattern extraction and modeling, which helps todesign model for moving object databases. This paper also proposes a method to predict the location of moving objects using mining association rules of movement patterns. The experiments are given to show that the proposed method is more accurate when used in combination with the motion function prediction method.